MOSQUE-BASED ZAKAT FITRAH: PROBLEMS OF IMPLEMENTATION - Pohan, Syahrial Hasanuddin; Rianto, Hartato; Agisra, Khalif Khairi (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This examination plans to decide the execution of the assortment and conveyance of zakat fitrah which has been done by mosques in Binjai City. This exploration will audit top to bottom the zakat assortment and strengthening programs. This examination additionally contains an evaluative component, to give an assessment to mosque managers viewing the viability and productivity as well as the advantages got by mustahik from the execution of the zakat fitrah dispersion program. This examination utilizes a subjective exploration strategy. The creator will make sense of top to bottom the discoveries that the creator has acquired in the field, and afterward give a translation, and orchestrate it deliberately so it is straightforward. Responsibility for the administration of infaq zakat as far as strategy making is great, where the mosque's amil or BKM generally hold gatherings when strategy choices are made, however they are never reported in a composition and get formal endorsement. The system for gathering and dispersing zakat fitra is great and responsible.